Monitoring of thermal changes in meat by synchronous fluorescence spectroscopy. (January 2016) - Sahar, Amna; Rahman, Ubaid ur; Kondjoyan, Alain; Portanguen, Stephane; Dufour, Eric
Highlights: Monitoring of thermal changes in meat. Study of Maillard and oxidation reactions in meat. Development of non-destructive technique to study heating process in meat. Synchronous fluorescence spectroscopy as rapid tool to investigate cooking kinetics. Use of chemometrics and spectroscopy in food studies. Abstract: Here we report the potential of synchronous front-face fluorescence spectroscopy in combination with chemometric tools to detect thermal changes in cooked meat. Samples of bovine meat ( Longissimus dorsi muscle) were cooked at 66, 90 & 237 °C for 0, 1, 2, 5, 7, and 10 min. Synchronous front-face fluorescence spectra were collected on meat samples in the excitation wavelength range of 250–550 nm using offsets (Δ λ ) of 20, 30, 40, 50, 60, 70, 80, 90, 100, 110, 120, 130, 140, 150, and 160 nm between excitation and emission wavelengths. The data from the synchronous fluorescence landscape containing 1080 spectra were analyzed using PCA & PARAFAC models. PCAs were applied to determine the potential of synchronous spectra to differentiate these samples as a function of cooking time and to retrieve additional information from different offset values. These results confirmed that the synchronous fluorescence spectra provide information related to the molecular structure of meat, allowing classification of samples as a function of cooking time & temperature. The best PARAFAC model was obtained with 3 components, having 55% core consistency values and 98% of the explained variance. The loading profiles of 1st, 2nd and 3rd components had an optimal Δ λ of 60, 30 and 80 nm, respectively, allowing the determination of excitation (exc.) and emission (em.) maxima wavelengths of 1st (fluorescence band at about exc.: 291 & em.: 351), 2nd (exc.: 297 nm & em.: 327 nm) and 3rd (exc.: 468 nm & em.: 548 nm) components. Loadings and scores of the PARAFAC model developed from the synchronous front-face fluorescence spectra enabled us to get information regarding the changes occurring in meat fluorophores during cooking of meat at 66, 90 & 237 °C from 0 to 10 min.